Dampak Pengelolaan Sumberdaya Manusia Terhadap Semangat Kerja Karyawan PT Bukit Jaya Abadi Surabaya - Susilowati, Sri; Farida, Ilya (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2016)
This research aims to know and analyze the impact human resource management in simultan and partial that influence toward employees morale of PT Bukit Jaya Abadi Surabayya. And find out the most dominan variable that influenced.The population of this research is the permanent employes which has about 95 personal there.method sampling used stastitied random sampling technical with 75 sample.Variable of this research include the variable of human resource management (X), consisting variable of selection (X ), Development (X 2 ), compensation (X 3) , maintance (X ), with significant (α) 5%. Analysis model, which is used is Multiple Regression Analysis that F-tes and t-test.Based on the research results shows the F-test that human resource management (X), including of Selection (X 1 ), Development (X 2 ), Compensation (X 90 3) 4 , Maintance (X ) variable in simultan that influenced toward employees morale (Y). It is proven F-count 6,148 > F-table 2,5 . while F-test, that influence the employees morale (Y) it is prove t-count -3.258 > t- tabel 1.6669 with significant 0,000. Based on the research results shows the t-test that Selection (X 4 1 ) and Maintance (X ) variable in partial that influenced toward employees morale (Y). It is proven, that Selection (X ) t-count 3,258 > t-table-1,666 with significant 0,002, wile It is proven, that Maintance (X 1 4 ) variable t-count -2,786 > t-table-1,6669 with significant 0,007. Selection (X ) is the most dominan variable that influenced toward employees morale (Y). Which contribute the whole variable on the variation employees morale is 26,01%, that is R 2 =0,2601. While the rest of a big 73,99% that influenced variable other that don’t exist in this research. Keywords: Human, Resource, Management, Employees, Morale